2019
DOI: 10.1016/j.plaphy.2018.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of UV-B stress induced flavonoids by biotic stress: Is there reciprocal crosstalk?

Abstract: Plants respond to abiotic UV-B stress with enhanced expression of genes for flavonoid production, especially the key-enzyme chalcone synthase (CHS). Some flavonoids are antioxidative, antimicrobial and/or UV-B protective secondary metabolites. However, when plants are challenged with concomitant biotic stress (simulated e.g. by the bacterial peptide flg22, which induces MAMP triggered immunity, MTI), the production of flavonoids is strongly suppressed in both Arabidopsis thaliana cell cultures and plants. On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 90 publications
0
31
1
Order By: Relevance
“…Under UV-B or excessive light stress, flavonoids are induced to provide sunscreens, antioxidants and/or antimicrobials (Schenke et al, 2019). MAMP signaling specifically suppresses UV-B-or sucrose-inducible flavonol biosynthesis in Arabidopsis (Saijo et al, 2009;Schenke et al, 2019), while it induces numerous defenserelated metabolites (e.g. phytoalexins, coumarin or lignin).…”
Section: High Light and Uv-b Stressmentioning
confidence: 99%
“…Under UV-B or excessive light stress, flavonoids are induced to provide sunscreens, antioxidants and/or antimicrobials (Schenke et al, 2019). MAMP signaling specifically suppresses UV-B-or sucrose-inducible flavonol biosynthesis in Arabidopsis (Saijo et al, 2009;Schenke et al, 2019), while it induces numerous defenserelated metabolites (e.g. phytoalexins, coumarin or lignin).…”
Section: High Light and Uv-b Stressmentioning
confidence: 99%
“…Considering that wounding and pathogen invasion also mechanically disrupt membranes and cell walls (Chen et al, 2016), these pathways may be signaling remodeling of cellular structures and the microtubule network in spaceflight. Flg22 application to Arabidopsis cell cultures and induction of MAMP-triggered immunity also has the effect of redistributing flavonoid compounds from biosynthetic processes important to oxidative stress response processes to the production of compounds important to defense (Schenke et al, 2019). Genes associated with the production of phenylpropanoids are less-represented among the spr1 DEGs downregulated in spaceflight compared to Col-0, although they are also more highly represented among spr1 DEGs downregulated across development in spaceflight (Figures 6B, 7B).…”
Section: Spr1 Mutation Produces a Decrease In Differential Gene Exprementioning
confidence: 99%
“…In Salvia miltiorrhiza , the silencing of the CHS gene enhanced the concentration of the resistance‐related phenolic substances and decreased the concentration of flavonoids (Schenke et al ). The changes from flavonoid synthesis to stilbenes via CHS downregulation and STS upregulation were observed in grape cell culture in response to fungal elicitors (Mutawila et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis , MYB4 acted as a critical regulator to alter the fluxes of intermediate products into the anthocyanin or lignin pathways. The upregulation of MYB4 slowed the biosynthesis of anthocyanin, whereas it induced the biosynthesis of lignin (Allan and Espley , Schenke et al ). Therefore, this study indicated that MYB4 plays a critical role in regulating the functional genes CHS , CCR and CAD , and as a result, inhibits the biosynthesis of anthocyanin.…”
Section: Discussionmentioning
confidence: 99%